The Mental Health Crisis of Unfulfilled Needs in Black Swan Movie by Darren Aronofsky - Rosalia; Winarsih, Sri; Istiqomah, Nurul; Sijabat, Survey (PT. Inovasi Teknologi Komputer, 2024)
health crisis that the main character, Nina Sayers, faces. The movie presents Nina, a talented ballerina, as she struggles to embody the dual roles of the White Swan and Black Swan in a high-stakes ballet performance. This research used qualitative research. The data in this research is collected by watching the movie to collect information on the data, making notes of each dialogue or scene, and even a paragraph that contains a hierarchy of needs using the theory of Abraham Maslow, which classifies the data based on the hierarchy of needs. The research results are the main character, Nina, who finds it challenging to fully take on the Black Swan role because of her inadequate social life and the absence of romantic and emotional bonds required for the part. Her mother's excessive protectiveness and high expectations trap her, concentrating her attention solely on her ballet career and stifling other areas of her life. The movie highlights mental health crises, focusing on disorders caused by work pressure and perfectionism, conflicts between personal identity and societal expectations, feelings of isolation, and a lack of social support